Photovoltaic Ge/Si quantum dot detectors operating in the mid-wave atmospheric window (3 to 5 μm) - Yakimov, Andrew (Springer, 2012)
Ge/Si quantum dots fabricated by molecular-beam epitaxy at 500°C are overgrown with Si at different temperatures T(cap), and effect of boron delta doping of Si barriers on the mid-infrared photoresponse was investigated. The photocurrent maximum shifts from 2.3 to 3.9 μm with increasing T(cap)from 300°C to 750°C. Within the sample set, we examined devices with different positions of the δ-doping layer with respect to the dot plane, different distances between the δ-doping layer and the dot plane d, and different doping densities p(B). All detectors show pronounced photovoltaic behavior implying the presence of an internal inversion asymmetry due to the placing dopants in the barriers. The best performance was achieved for the device with T(cap )= 600°C, p(B )= 12 × 10(11)cm(−2), and d = 5 nm in a photovoltaic regime. At a sample temperature of 90 K and no applied bias, a responsivity of 0.83 mA/W and detectivity of 8 × 10(10) cm Hz(1/2)/W at λ = 3.4 μm were measured under normal incidence infrared radiation.